Dimensi Pragmatisme Politik Sebagai Bagian Dari Kebutuhan Masyarakat Modern Dalam Kontestasi Pemilu Tahun 2024 Di Kabupaten Lamongan (Studi Ilmu Psikologi Dalam Dimensi Politik Modern) - Burhan Hakim, Ahmad; Satryo Pringgo Sejati (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Democracy has become a political system that has been used massively in Indonesia since the reformation rolled in 1998. Elections are one of the major agendas of the government and state to be called a democratic country. In the 2024 election, there were allegations of pragmatic politics and transactional politics in Lamongan Regency. This is one of the important social facts amidst the rampant campaign about democratization in Indonesia. With this kind of incident, political costs are high, because there is or there is a lot of technical money rolling during the election. This study uses a descriptive qualitative research method supported by a literature study as part of the analytical tool to reveal facts and field findings in the study. Pragmatic attitudes and transactional political activities in Lamongan Regency do not appear in a vacuum but have become a massive social phenomenon and seem to be an open secret. Both politicians, legislative candidates and the community in Lamongan Regency consider these activities to be something that is not strange and ordinary, so that this pragmatic attitude cannot only be directed at politicians but also the majority of the community does want this. Thus, democracy is not only a matter of political development and the exchange of ideas about a welfare state, but on the other hand, it gives rise to high-cost politics due to transactional and pragmatic politics.